Effectiveness of reactive hepatitis therapy in injured with ballistic wounds - Kyrylo, Savichan (The Ukrainian Scientific Medical Youth Journal, 2022)
Reactive hepatitis complicates the treatment of ballistic wounds. The aim of our study was to study the clinical and pharmacoeconomic effectiveness of the treatment of reactive hepatitis in the wounded. A prospective study of 112 wounded servicemen with increased transaminase activity was randomized into three groups: group I received arginine glutamate intravenously for 10 days, group II received phosphatidylcholine intravenously for 10 days, and group III received standard treatment. In the presence of hypoalbuminemia, the wounded received intravenous infusions of albumin to normalize its level in serum. The initial level of alanine aminotransferases was 62.5 in group I patients [50.5; 80.0] IU / l, in the second group - 64.0 [48.5; 83.0] IU / l and 62.0 [47.0; 85.5] IU / l, respectively, in group III (p> 0.05 according to the Mann-Whitney test). In the period up to 14 days after injury, alanine aminotransferase levels decreased significantly in all groups (p <0.05 according to Wilcoxon’s test) and amounted to 38.5 in group I [34,0; 63.5] IU / l, in the second group 46.0 [32.0; 62.5] IU / l, in group III 50.0 [40.0; 78.0] IU / l (p = 0.014 according to the Mann-Whitney test compared to group I). In 14 and more days after injury in all groups the average concentration of alanine aminotransferases was significantly lower compared to the previous study period (p <0.05 according to Wilcoxon’s test): in group I the concentration of alanine aminotransferases was 33.0 [29,8; 40.0] IU / l (p = 0.048, p <0.001 according to the Mann-Whitney test in comparison with group II and III, respectively), in group II - up to 38.0 [31.0; 62.0] and in group III to 48.0 [39.5; 69.0] (p = 0.014 according to the Mann-Whitney test compared to group II). Also, there was a tendency to reduce the frequency of complications from internal organs: in 13% (8 of 63) patients of groups I and II, compared with 27% (13 of 49) of group III (p = 0.063). Significantly decreased both the duration of treatment in the intensive care unit: in group I (4.2 ± 1.8) days, compared with group III (7.4 ± 6.0) days, p = 0.012, and the duration of total hospital stay (20.4 ± 11.1) days for group I, compared with (29.7 ± 3.5) days for group III, p = 0.022. In the cost-effectiveness analysis of arginine glutamate and phosphatidylcholine regimens, a 2-fold better cost-effectiveness ratio was found in the group of reactive hepatitis wounded who received arginine glutamate.